Short-term benefits from central unit commitment and dispatch: Application to the Southern African Power Pool - Bowen, Brian Hugh (ProQuest Dissertations & Theses, 1998)
Electricity utilities in the Southern African region are conscious that gains could be made from more economically efficient trading but have had no tools with which to analyze the effects of a change in policy. This research is the first to provide transparent quantitative techniques to quantify the impacts of new trading arrangements in this region. The study poses a model of the recently formed Southern African Power Pool, built with the collaboration of the region's national utilities to represent each country's demand and generation/transmission system. The multi-region model includes commitment and dispatch from diverse hydrothermal sources over a vast area. Economic gains are determined by comparing the total costs under free-trade conditions with those from the existing fixed-trade bilateral arrangements. The objective function minimizes production costs needed to meet total demand, subject to each utility's constraints for thermal and hydro generation, transmission, load balance and losses. Linearized thermal cost functions are used along with linearized input output hydropower plant curves and hydrothermal on/off status variables to formulate a mixed-integer programming problem. Results from the modeling show that moving to optimal trading patterns could save between $70 million and $130 million per year. With free-trade policies the quantity of power flow between utilities is doubled and maximum usage is made of the hydropower stations thus reducing costs and fuel use. In electricity exporting countries such as Zambia and Mozambique gains from increased trade are achieved which equal 16% and 18% respectively of the value of their total manufactured exports. A sensitivity analysis is conducted on the possible effects of derating generation, derating transmission and reducing water inflows but gains remain large. Maximum economic gains from optimal trading patterns can be achieved by each country allowing centralized control through the newly founded SAPP coordination center. Using standard mixed integer programming solvers makes the cost of such modeling activity easily affordable to each utility in the Southern African pool. This research provides the utilities with the modeling tools to quantify the gains from increased trade and thereby furthers a move towards greater efficiency, faster economic growth and reduced use of fossil fuels.